A comparison of the present and proposed OR Department of Cardinal Santos Medical Center, using evidence-based design criteria - Dalmacio, Ronald John B. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2022)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/8893/7817